THE ANALYSIS OF REFORMING OF STRUCTURES OF RAILWAY TRANSPORT MANAGEMENT IN THE DEVELOPED COUNTRIES OF EUROPE - Barash, Yu. S. (Science and Transport Progress, 2003)
The article analyzes intermediate results of reforming the structures of railway transport management in developed European countries after adoption of the European Union’s declarations on the issue. The conclusion has been made that the governments of European countries have different attitudes toward the EU directives and do not always consider it necessary to reform the structure of railway transport management.